Towards Automated Design: Automatically Generating Modeling Elements with Prompt Engineering and Generative Artificial Intelligence - Kulkarni, Pranav Jayant; Tissen, Denis; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of NordDesign 2024)

The Venture Client Model and Its Challenges for Established Companies - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Kuhn, Arno; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Data from start to finish: A System Life Cycle Data Map - Tissen, Denis; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Toward Intelligent Generation of System Architectures - Von Heissen, Oliver; Hanke, Fabian; Mpidi Bita, Isaac; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Reference Architecture for the Integration of Prescriptive Analytics Use Cases in Smart Factories - Weller, Julian; Migenda, Nico; Naik, Yash; Heuwinkel, Tim; Kühn, Arno; Kohlhase, Martin; Schenck, Wolfram; Dumitrescu, Roman (Mathematics)
Prescriptive analytics plays an important role in decision making in smart factories by utilizing the available data to gain actionable insights. The planning, integration and development of such use cases still poses manifold challenges. Use cases are still being implemented as standalone versions; the existing IT-infrastructure is not fit for integrative bidirectional decision communication, and implementations only reach low technical readiness levels. We propose a reference architecture for the integration of prescriptive analytics use cases in smart factories. The method for the empirically grounded development of reference architectures by Galster and Avgeriou serves as a blueprint. Through the development and validation of a specific IoT-Factory use case, we demonstrate the efficacy of the proposed reference architecture. We expand the given reference architecture for one use case to the integration of a smart factory and its application to multiple use cases. Moreover, we identify the interdependency among multiple use cases within dynamic environments. Our prescriptive reference architecture provides a structured way to improve operational efficiency and optimize resource allocation.

On the Current State of Industrial Data Science: Challenges, Best Practices, and Future Directions - von Enzberg, Sebastian; Weller, Julian; Brock, Jonathan; Merkelbach, Silke; Panzner, Melina; Lick, Jonas; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Design decisions for integrating Prescriptive Analytics Use Cases into Smart Factories - Weller, Julian; Migenda, Nico; Enzberg, Sebastian von; Kohlhase, Martin; Schenck, Wolfram; Dumitrescu, Roman (Procedia CIRP)

Applying Artificial Intelligence in the Smart Factory: Lessons Learned from real-world use cases - Hartmann, Stefan; Brock, Jonathan; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)

Prescriptive Analytics Data Canvas: Strategic Planning For Prescriptive Analytics In Smart Factories - Weller, Julian; Migenda, Nico; Kühn, Arno; Dumitrescu, Roman

Using Multi-Modal LLMs to Create Models for Fault Diagnosis - Merkelbach , Silke; Diedrich , Alexander; Sztyber-Betley, Anna; Travé-Massuyès, Louise; Chanthery , Elodie; Niggemann , Oliver; Dumitrescu , Roman (Open Access Series in Informatics (OASIcs))

Technical Readiness of Prescriptive Analytics Platforms: A Survey - Niederhaus, Marvin; Migenda, Nico; Weller, Julian; Schenck, Wolfram; Kohlhase, Martin (2024 35th Conference of Open Innovations Association (FRUCT))

Challenges and Research Needs in the Offer Phase of Special Purpose Machinery and Plant Engineering – A Qualitative Study with Industry Experts - Wilke, Daria; Mansheim, Johanna; Dumitrescu, Roman (IEEE Engineering Management Review)

PID-Gen: Towards an Algorithm for the Generation of Random P&IDs - Merkelbach, Silke; Heuwinkel, Tim; Dumitrescu, Roman (2024 IEEE 29th International Conference on Emerging Technologies and Factory Automation (ETFA))

Investigation of validation methods for system design in the B2B sector - Humpert, Lynn; Wilke, Daria; Tissen, Denis; Rummney, Johannes; Anacker, Harald; Dumitrescu, Roman (2024 IEEE International Systems Conference (SysCon))

Framework for the Selection of Systems Engineering Modelling Languages and Methods for Special Purpose Machinery - Wilke, Daria; Humpert, Lynn; Suwal, Pragita; Dumitrescu, Roman (Proceedings of NordDesign 2024)

Intelligent Part Comparison in Computer Aided Design - Hanke, Fabian; Moallim, Karan; Bernijazov, Ruslan; Demir, Riza; Brunnhausser, Jorg; Dumitrescu, Roman; Lindow, Kai (Proceedings of NordDesign 2024)

Numerical modeling of clamp load relaxation of plastic nuts under varying moisture and fiber content - Wippermann, Jan; Meschut, Gerson
This study presents a numerical approach using a 3D finite element model to quantify the remaining clamp load of a plastic nut joint after a specific time. The viscoelastic relaxation of a thermoplastic nut, which is predominantly screwed on a welding stud, is described by a material card using Prony Series. Prony Series are derived from experimental Dynamical Mechanical Analysis with different moisture and fiber contents of the thermoplastic. Since plastic nuts usually do not have preformed threads, the increased temperatures and resulting stresses from the thread-forming process are considered in the simulation. Firstly, the FE model is verified by substrate stress relaxation tests. Subsequently, experimental clamp load measurements with miniature compression load cells verify the clamp load prediction. Finally, the developed model is used to analyze the clamp load distribution within the threads

Effect of Water Absorption on the Clamp Load of Plastic Nuts - Wippermann, Jan; Meschut, Gerson (Proceedings of the Munich Symposium on Lightweight Design 2023)

Anwendung und Integration des Application Lifecycle Managements im Produktlebenszyklus-Ergebnisse einer Industrie-Studie - Wyrwich, Fabian; Tschirner, Christian; Bohnenkamp, Tinus; Hovemann, Aschot; Dumitrescu, Roman (Tag des Systems Engineering 2024)

Portals across domains: A data analysis task and documentation canvas for data-driven model-based systems engineering - Tissen, Denis; Wiederkehr, Ingrid; Bernijazov, Ruslan; Koldewey, Christian; Dumitrescu, Roman